Assessment of antibodies against surface and outer membrane proteins of Anaplasma phagocytophilum in Lyme borreliosis and tick-borne encephalitis paediatric patients - Krbková, L; Homola, L; Hlaváčová, A; Mikolášek, P; Bednářová, J; Čermáková, Z (Epidemiology and infection, 2016)
To examine evidence of positive antibodies against immunogenic proteins of Anaplasma phagocytophilum in patients with other tick-borne infections and to diagnose possible co-infections, 412 serum specimens were tested by immunoblotting using three specific Anaplasma antigens: surface proteins p44 and Asp62 and outer membrane protein A (OmpA). In total, 284 serum samples from children with Lyme borreliosis and 12 serum samples from children with tick-borne encephalitis were tested. Sera from patients with viral aseptic meningitis (n = 47) and from blood donors (n = 69) were used as controls. Among all serum specimens from patients with tick-borne infections submitted for this study, six samples (2·0%) showed positive IgM reactions and seven samples (2·4%) were IgG positive for A. phagocytophilum by immunoblot. Borderline reactivity was found in 30 samples (10·14%) for IgM and 36 samples (12·2%) for IgG. The difference between patients and blood donors was statistically significant for IgM (P = 0·006) and for IgG (P = 0·0007) antibodies. A statistically significant result was obtained for IgG (P = 0·02) but not for IgM between patients and children with aseptic meningitis. Immunoblot using three specific antigens provides novel information about the positivity of antibodies to A. phagocytophilum in children with other tick-borne infections. Taking into account clinical and laboratory findings of children despite antibody positivity, no case of human granulocytic anaplasmosis was demonstrated.
Keywords: Membrane Proteins; anaplasmóza; Humans; Encephalitis, Tick-Borne; koinfekce; klíšťová encefalitida; dítě; Coinfection; Child; Lyme Disease; lymeská nemoc; Female; protilátky bakteriální; Blotting, Western; tick-borne encephalitis; lidé; outer membrane protein A; bakteriální proteiny; major surface proteins; Bacterial Outer Membrane Proteins; Antibodies, Bacterial; human granulocytic anaplasmosis; předškolní dítě; proteiny vnější bakteriální membrány; ženské pohlaví; Male; Anaplasmosis; Adolescent; Czech Republic; Lyme borreliosis; Bacterial Proteins; membránové proteiny; Česká republika; western blotting; mužské pohlaví; Child, Preschool; mladiství; Anaplasma phagocytophilum